INTERVENSI KEBIJAKAN POLITIK DALAM REKONSTRUKSI KURIKULUM PENDIDIKAN AGAMA ISLAM: TELAAH KRITIS DAN KONTEKSTUAL - Kurniasih, Dede Dwi; Khoriyadi, Imam; Suratin, Sonia Isna; Fakhrurridha, Hujjatul (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
This article aims to critically examine the intervention of political policies in the process of reconstructing the Islamic Religious Education (PAI) curriculum in Indonesia, by highlighting how the dynamics of political power play a role in shaping the direction and content of the curriculum. This study uses a literature study method, by examining various secondary sources such as education policy documents, PAI curricula from time to time, academic journals, and literature relevant to the relationship between politics and education. The results of the study show that changes in the PAI curriculum are often inseparable from the influence of practical politics, where the ideological agenda of power influences the content of values, teaching materials, and pedagogical approaches used. In this context, the PAI curriculum tends to be a tool for legitimizing power, not merely as a means of developing the character and spirituality of students. The novelty of this study lies in the critical review approach used to examine the curriculum as a socio-political product, not only as an academic construction. In addition, this article contributes by offering a contextual approach in developing the PAI curriculum that is more responsive to the needs of the times, upholds the values ??of Islam rahmatan lil 'alamin, and emphasizes the importance of the involvement of educational actors who are independent of political interests in the process of formulating the curriculum.